A multi-analytical geoarchaeological study of flint procurement strategies in southern Iberia - José Luis Ramírez-Amador; Eduardo Molina-Piernas; José Ramos-Muñoz; Salvador Domínguez-Bella (Scientific Reports)
Abstract The study of lithic raw material procurement strategies provides critical insights into the socio-economic organization and territorial mobility patterns of prehistoric societies. This research applies a pioneering geoarchaeological approach by combining advanced analytical techniques, including polarized optical microscopy (POM), cathodoluminescence microscopy (CL), scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray fluorescence (XRF) to characterize archaeological and geological flint samples from Ardales Cave and Sima de las Palomas in southern Iberia. The results reveal a systematic exploitation of secondary deposits in nearby fluvial terraces, within a predominantly local procurement framework, occasionally complemented by supra-regional acquisition episodes. Petrographic analysis, enhanced by cathodoluminescence images, enabled an unprecedented differentiation of flint varieties and identification of their diagenetic processes, significantly refining sourcing and characterization methods in geologically complex regions such as the Betic Cordillera. This study represents a key methodological advance in geoarchaeology, demonstrating the high potential of cathodoluminescence applied to flint analysis and establishing a robust analytical framework to interpret mobility patterns, territorial interaction, and technological resource management in prehistoric contexts.